The Mamluk-Ottoman transition: continuity and change in Egypt and Bilād al-Shām in the sixteenth century, 2 - Conermann, Stephan; Şen, Gül (Ottoman studies, 2022)
While the Ottoman conquest of the Mamluk realm in 1516-17 doubtlessly changed the balance of political power in Egypt and Greater Syria, the changes must be seen as a wide-ranging transition process. The present collection of essays provides several case studies on the changing situation during the fifteenth and sixteenth centuries and explains how the reconfiguration of political power affected both Egypt and Greater Syria. With reference to the first volume (2017), this second volume continues the debate on key issues of the transition period with contributions by scholars from both Mamluk and Ottoman studies. By combining these perspectives, the authors provide a more comprehensive and nuanced picture of the process of transformation from Mamluk to Ottoman rule.